Chili 1977-2005 : pour une lecture historienne de la « longue transition à la démocratie de marché » - Stéphane Boisard (Les Cahiers de Framespa)
There has been much debate about Transition to the democracy in Chile, “achieved or not”, “complete or incomplete”, democracy with adjectives or not. In this country, the periodisation of the transition remains complicated because every outstanding political event gives it a new start, transforming transitology - the science of transitions to democracy - into a storytelling in itself that characterizes the post-dictatorial period more than a true transitional period from one state to another. This article proposes to start from the concept of "market democracy" to think over this topic and historicize the "long" Chilean transition. Two phases can be considered : a first phase of "institutional transition" from 1977 to 1998, and a second phase of "political transition" from 1998 to 2005, the latter leading to a real democratisation of society wiht a profound change in the 1980 Constitution but also to an ideological victory for the Chilean Right-wing insofar as its development model has not been questionned.